Primary diagnosis of dilated cardiomyopathy in combination with myocardial non-compaction in an elderly patient: a case report - Yu. V. Vakhnenko; E. A. Bagdasaryan; D. A. Savchenko (Российский кардиологический журнал)
The classifications of the World Health Organization, the European Society of Car-diology and the American Heart Association indicate the existence of several phenotypes of myocardial non-compaction (MnC) with specific structural and functional abnormalities. The MnC+dilated cardiomyopathy (DCM) phenotype is considered one of the most severe variants. Disputes continue about whether to regard MnC as an independent disease or as a consequence of DCM and heart failure. In other words, MnC remains one of the most mysterious heart diseases. As an illustration of MnC+DCM phenotype, the authors offer a case of a patient with cardiovascular disease from her youth, but maintained a satisfactory state of health and performance until her old age. Symptoms of arrhythmia and heart failure with massive pericardial effusion were first described in her at the age of 66, which is uncharacteristic for this MnC phenotype. Attention is drawn to the difficulties of differential diagnosis of MnC due to the non-specificity of clinical performance, the role of echocardiography in the recognition of the disease and predictors of its unfavorable outcome. The fact that the patient, even when typical signs of MnC were detected during echocardiography, initially had coronary artery disease as the main diagnosis, indicates the relevance of publishing another case report on this rare pathology in order to improve the awareness of cardiologists and general practitioners.